HEALTHY LIVING PROJECT: ASSESSMENT AND FORWARDING OF HEALTH PROMOTION ACTIONS AT SCHOOLS IN GOIÂNIA, GO (Fiep Bulletin - online, 2012)
The school is considered an important setting for health promotion and adoption of healthy habits. The Healthy Living Project (HLP) is the result of partnership between university and health and education sector and aims to stimulate and implement behaviors that facilitate healthy living, through the adoption of physical activity throughout life, the healthy food choices, abandonment and / or rejection of practices harmful to health at the school community. The objective of this paper is to present the main results obtained within the project in the period between 2007 and 2011. It is a quantitative and qualitative descriptive study conducted from secondary analysis of data from two Master studies: Physical activity and food choices of students in the eastern region of Goiânia - GO and Healthy eating in schools: a collective construction? Both studies show that the initial results of the HLP were not achieved. These findings, analyzed with other documents from the project (records of meetings, interviews with key informants and reports) focusing on process and intermediate results are explained by the poor physical structure in most schools, work overload, the lack of knowledge about the subject and even the non-recognition of the influence of the project in some healthy activities at schools. Critical thinking on the evaluation process of the HLP led to the redesign of their actions through 1) the reorganization of the working groups, 2) participatory planning with improved monitoring, 3) interprofessional continuing education, and, 4) conducting participatory evaluation studies. The articulation of the HLP with the government's Health in School Program should be expanded to improve financial and human resources toward health promotion within the school environment.
Keywords: physical activity; healthy food and health promotion